Formal total synthesis of macarpine via a Au(I)-catalyzed 6-endo-dig cycloisomerization strategy - Fu, Jiayue; Li, Bingbing; Zhou, Zefang; Cheng, Maosheng; Yang, Lu; Liu, Yongxiang (Beilstein Journal of Organic Chemistry, 2022)
The formal total synthesis of macarpine was accomplished by the construction of a naphthol intermediate in Ishikawa’s synthetic route with two different synthetic routes. The convergent synthetic strategies feature the utilization of Au(I)-catalyzed cycloisomerizations of a 1,5-enyne and alkynyl ketone substrates, which were prepared by Sonogashira coupling reactions.
Keywords: benzo[c]phenanthridine alkaloids; 1,5-enyne; formal total synthesis; gold catalysis; macarpine

(untitled) - Slaninová, I.; Slunská, Z.; Šinkora, J.; Vlková, M.; Táborská, E. (Pharm. Biol. (Abingdon, U. K.), 2007)

(untitled) - Al-Snafi, A. E. (Indo Am. J. Pharm. Sci., 2017)

(untitled) - Cheng, P.; Zeng, J. (Chin. J. Org. Chem., 2012)

(untitled) - Orhan, I.; Özçelik, B.; Karaoğlu, T.; Şener, B. (Z. Naturforsch., C: J. Biosci., 2007)

(untitled) - Wang, Q.; Dai, P.; Bao, H.; Liang, P.; Wang, W.; Xing, A.; Sun, J. (Exp. Ther. Med., 2017)

(untitled) - Balažová, A.; Urdová, J.; Forman, V.; Mučaji, P. (Molecules, 2020)

(untitled) - Gaziano, R.; Moroni, G.; Buè, C.; Miele, M. T.; Sinibaldi-Vallebona, P.; Pica, F. (World J. Gastrointest. Oncol., 2016)

(untitled) - Pica, F.; Balestrieri, E.; Serafino, A.; Sorrentino, R.; Gaziano, R.; Moroni, G.; Moroni, N.; Palmieri, G.; Mattei, M.; Garaci, E.; Sinibaldi-Vallebona, P. (Anti-Cancer Drugs, 2012)

(untitled) - Schmeller, T.; Latz-Brüning, B.; Wink, M. (Phytochemistry, 1997)

(untitled) - Slaninová, I.; López-Sánchez, N.; Šebrlová, K.; Vymazal, O.; Frade, J. M.; Táborská, E. (Biol. Cell, 2016)

(untitled) - Hanaoka, M.; Cho, W. J.; Yoshida, S.; Fueki, T.; Mukai, C. (Heterocycles, 1989)

(untitled) - Ishikawa, T.; Saito, T.; Ishii, H. (Tetrahedron, 1995)

(untitled) - Solorio-Alvarado, C. R.; Echavarren, A. M. (J. Am. Chem. Soc., 2010)

(untitled) - Singh, S.; Samineni, R.; Pabbaraja, S.; Mehta, G. (Angew. Chem., Int. Ed., 2018)

(untitled) - Fu, J.; Li, B.; Wang, X.; Liang, Q.; Peng, X.; Yang, L.; Wan, T.; Wang, X.; Lin, B.; Cheng, M.; Liu, Y. (Chin. J. Chem., 2022)

(untitled) - Huang, Q.; Wang, P.; Tian, Y.; Song, N.; Ren, S.; Tao, J.; Hang, K.; Li, M. (Synlett, 2015)

(untitled) - Xie, F.; Zhang, B.; Chen, Y.; Jia, H.; Sun, L.; Zhuang, K.; Yin, L.; Cheng, M.; Lin, B.; Liu, Y. (Adv. Synth. Catal., 2020)

(untitled) - Liu, X.-J.; Zhou, S.-Y.; Xiao, Y.; Sun, Q.; Lu, X.; Li, Y.; Li, J.-H. (Org. Lett., 2021)

(untitled) - Hashmi, A. S. K.; Rudolph, M. (Chem. Soc. Rev., 2008)

(untitled) - Rudolph, M.; Hashmi, A. S. K. (Chem. Soc. Rev., 2012)

(untitled) - Pflästerer, D.; Hashmi, A. S. K. (Chem. Soc. Rev., 2016)

(untitled) - Hashmi, A. S. K.; Frost, T. M.; Bats, J. W. (J. Am. Chem. Soc., 2000)

(untitled) - Hashmi, A. S. K.; Rudolph, M.; Siehl, H.-U.; Tanaka, M.; Bats, J. W.; Frey, W. (Chem. – Eur. J., 2008)

(untitled) - Dankwardt, J. W. (Tetrahedron Lett., 2001)

(untitled) - Schießl, J.; Schulmeister, J.; Doppiu, A.; Wörner, E.; Rudolph, M.; Karch, R.; Hashmi, A. S. K. (Adv. Synth. Catal., 2018)

(untitled) - Schießl, J.; Schulmeister, J.; Doppiu, A.; Wörner, E.; Rudolph, M.; Karch, R.; Hashmi, A. S. K. (Adv. Synth. Catal., 2018)

(untitled) - Song, L.; Tian, G.; Van der Eycken, E. V. (Chem. – Eur. J., 2019)

(untitled) - Guan, Y.; Lu, Z.; Yin, X.; Mohammadlou, A.; Staples, R. J.; Wulff, W. D. (Synthesis, 2020)

(untitled) - Makra, F.; Rohloff, J. C.; Muehldorf, A. V.; Link, J. O. (Tetrahedron Lett., 1995)